Lifestyle, nutrition, the presence of bad habits and the level of physical preparedness of adolescents aged 14-15 living in Siberia. - Г.В. Иванова; О.Я. Кольман; А.Н Иванова; М.Д Кудрявцев (H.S. Skovoroda Kharkiv National Pedagogical University, 2018)
Ivanova G. V., Kolman O. Ya., Ivanova A.N., Kudryavtsev M. D. Lifestyle, nutrition, the presence of bad habits and the level of physical preparedness of adolescents aged 14-15 living in Siberia. The purpose of the work is to reveal the peculiarities of the way of life, nutrition, the presence of bad habits and the level of physical preparedness of adolescents aged 14-15 living in Siberia. Material and methods. Methods of research: analysis and generalization of data from scientific and methodological and specialized literature, pedagogical observations, questionnaire survey of students of Gymnasium No. 9 in Krasnoyarsk, methods of mathematical statistics, study of endurance indices of students of gymnasium No. 9. The schoolchildren's endurance was assessed on a 6-minute run GP Bogdanov). Results. It is revealed that in percentage terms girls smoke more than boys. The age of onset of smoking in boys is 5 years, and in girls 9 years. But at the same time, the number of girls who smoke has risen to 13 years. By the age of 15, the number of girls who had lit cigarettes exceeded the male part by 4 times. And the number of first-time smoking boys decreased by 3 times compared to 13-year-olds. When answering the question "Do you drink beer?" 20 people answered that they drink "sometimes". As a result of a questionnaire survey on the peculiarities of nutrition of students of the 8th grade, it was found that schoolchildren most rarely consume such valuable products within a week from the point of view of rational nutrition, like egg, cottage cheese, cereals, fish, milk and yogurt. Most students prefer to receive pizza, sausage in the test, hamburgers, salads, pies, belyasha, juices, fruits in the school cafeteria. Smoking teens show significantly lower results than non-smokers. Teenagers who professionally engage in sports and violate the sports regime (smokers), although they show a higher percentage in comparison with "non-athletes", but lose in stamina to non-smoking athletes. Conclusion. Dangerous tendencies in adolescents of Siberia regarding the prevalence of unhealthy lifestyle, irrational nutrition, the presence of bad habits and a low level of endurance development are revealed.